(untitled) (Revista de Física Médica, 2024)
The Patient Safety Commission of the Spanish Medical Physics Society was set up in 2021 with the aim of improving the safety of patients exposed to medical procedures involving ionising radiation. To establish the commission’s lines of work, a nationwide survey was conducted as a starting point to determine the state of implementation of quality management and patient safety tools in Medical Physics departments and in medical services that use ionising radiation. The answers provided by the respondents show that Radiotherapy is the area with the greatest involvement of medical physicists, which has led to a greater implementation of quality and patient safety management tools in this area compared to the areas of Radiology and Nuclear Medicine. The participants consider that the Patient Safety Commission can help to improve quality and safety in clinical fields where ionising radiation is used by developing practical guides, teaching activities and IT applications in collaboration with the corresponding scientific societies.